Reference Values for Serum Calcium in Neonates Should Be Established in a Population of Vitamin D-Replete Subjects - Levaillant, Lucie; Linglart, Agnès; Gajdos, Vincent; Benachi, Alexandra; Souberbielle, Jean-Claude (The journal of clinical endocrinology and metabolism, 2024)
Serum calcium is frequently measured during the neonatal period, and it is known to be influenced by the vitamin D status. We hypothesized that the 25-hydroxyvitamin D (25OHD) concentration may influence the lower limit of the serum calcium normal range in neonates. We included in our prospective cohort study 1002 mother-newborn pair recruited from April 2012 to July 2014, in 2 centers located in the neighborhoods of Paris, France, whose serum calcium was measured at 3 days of life. We established, after exclusion of outliers, a 95% CI for serum calcium (i) in our whole population of 1002 neonates; (ii) in neonates with a cord blood 25OHD concentration ≥ 30 nmol/L; and (iii) in those with a 25OHD ≥ 50 nmol/L. The mean serum total calcium was 2.46 ± 0.13 nmol/L (95% CI: 2.19-2.72 mmol/L), 2.47 ± 0.25 mmol/L (95% CI: 2.22-2.72 mmol/L), and 2.50 ± 0.25 mmol/L (95% CI: 2.25-2.75 mmol/L) in the whole group, in the 514 neonates with 25OHD ≥ 30 nmol/L, and in the 202 neonates with 25OHD ≥ 50 nmol/L respectively. The lower limit of the 95% range was significantly higher in neonates with 25 OHD ≥ 30 nmol/L (P < 0.05) and ≥ 50 nmol/L (P < .001) than in the entire cohort. We show that the lower limit of the normal serum calcium range is higher in groups with a higher 25OHD than in unselected subjects. We propose that the reference range for serum calcium in neonates is 2.25 to 2.75 mmol/L.